2018
DOI: 10.15561/18189172.2018.0308
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sports training programme on juvenile sports dancers motivation

Abstract: Purpose:Lately, the researchers have paid more and more attention to the issues of sport motivation of exercising schoolchildren, but there are few scientific studies drawing the attention of researchers to sports training programme effect on juvenile sports dancers motivation. Purpose: to verify the effectiveness of sports training programme on the expression of juvenile (9-11 years old) sports dancers sport motivation. Material:A scheme of the research of three groups was applied by using the initial and fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Motivation determines why young dancers perform the same task differently under the same conditions and why gifted children perform the same task differently. For example, (Uspuriene, 2015;Uspuriene & Sniras, 2018) have found that technical training is often the predominant focus of competitive dance training, and that monotonous, uniform tasks can lead dancers to be overly competitive or even unwilling to dance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivation determines why young dancers perform the same task differently under the same conditions and why gifted children perform the same task differently. For example, (Uspuriene, 2015;Uspuriene & Sniras, 2018) have found that technical training is often the predominant focus of competitive dance training, and that monotonous, uniform tasks can lead dancers to be overly competitive or even unwilling to dance.…”
Section: Discussionmentioning
confidence: 99%
“…The motivation of young dancers (12-14 years old) was measured with The sport motivation scale (SMS) (Pelletier et al, 1995), which is adapted and validated for dancers (Ušpurienė, 2015;Uspuriene & Sniras, 2018). This scale is based on the Self-determination theory (Deci, Ryan, 1985;2009), which states that motivation has two origins: intrinsic and extrinsic.…”
Section: Research Sample and Proceduresmentioning
confidence: 99%
“…In other words, students participate in physical education activities entirely out of their needs, desires, and cognition, such as the desire to obtain physical pleasure and psychological pleasure or stimulation from physical education activities, or to satisfy the active, curious, or competitive mentality [ 4 ]. The latter refers to physical education activities generated from external factors instead of students themselves; that is, students’ participation in physical education activities is caused by external incentives or pressure, such as wishing to be praised, rewarded, or avoiding punishment [ 5 ]. Generally, students’ physical education activities are driven by both internal and external motivations, but at a particular moment, students are often driven by one motivation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%